Using game theory to determine the point of interest sharing in a bilateral contract - Kiani Ghaleh no, Rouhollah (International Journal of Business Management and Entrepreneurship, 2024)
The purpose of this research is to protect the interests of the two parties to the contract, who jointly or separately have requirements and restrictions and expect the details of the agreement to be such that their interests are protected. In fact, this research provides a calculation method for agreement in contracts, which is very frequent in the real world and is a bridge to communicate between humanities and computing sciences. Methodology: In this research, a model based on the game theory mechanism is proposed for the equilibrium point. To clarify the details of the contract, the 4p, 7p, ... models that are in the marketing mix are considered. Binary numbers are used to determine game strategies. And finally, a mathematical model is presented to calculate the consequences of the game. Therefore, research is an interdisciplinary work. Findings and results: The number of strategies in such games is exponential in nature, and with the increase in the number of variables, the problem will become very large and difficult, and its solution will be a challenge. In addition to modeling the problem, the solution algorithm of this model is also presented has been done, and real-world examples are given to clarify the issue.